Determination of the Content of Mercury and Cadmium in Fish of Rivers (Chakvistskali, Bartskhana, Chorokhi, Ajaristskali and Kubistskali) - Mirangula Liparteliani; Tea Mchedluri; Lali Koptonashvili (Web of Journals Publishing, 2023)
The major problem of our time is the contamination of reservoirs with heavy metals, which is mainly a result of anthropogenic impact. One of the particularly toxic metals is cadmium, which, as a result of sorption on suspended particles, forms complex compounds with organic substances and moves in this form. They pollute the water. They are characterized by special toxicity for hydrobionts and humans and have a significant negative impact on freshwater ecosystems, as they may transform into more dangerous forms in the environment. They can poison and/or reduce the number of aquatic organisms, pollute natural landscapes, disrupt and reduce the biodiversity of aquatic ecosystems (Mchedluri, T. 2020). Based on the above, we considered it urgent to study the Cd pollution of the rivers of the Black Sea Basin (the Chakvistskali, the Chorokhi, the Bartskhana, the Adjaristskali, the Kubistskal) and its contents in the body of fishes. Based on the results of our research, it was found that it is possible that the water taken from a specific point is not contaminated with Cd, but a certain amount of cadmium is accumulated in the body of fish taken from the same river. During the fall season of 2019-2020, the concentrations of cadmium in the bodies of fish taken from the rivers as research objects were small, but still recorded. The results of the analysis show that the highest content was found in the fish of the rivers Chorokhi and the Adjariskali. In our opinion, this is due to the fact that fish easily absorb cadmium from the water and it accumulates in the body. It is important to note that their concentration is much lower than MAC. Thus, the ecosystems of the mentioned river are not polluted by cadmium. Consequently, it is almost impossible to pollute rivers, water ecosystems, fish, hydrobionts and their populations, reservoir biocenoses with the mentioned heavy metals
Keywords: The Black Sea, heavy metals, cadmium, mercury.